The Effect Of Social Capital On Interest In Entrepreneurship With Self-Efficiency - andarweni astuti; Puji Hardati (Journal of Geography Science and Education, 2022)
The formulation of the problem in this study is how the influence of social capital on the interest in entrepreneurship with self-efficacy in STPKat students. This study aims to analyze the effect of student social capital on entrepreneurial interest with self-efficacy. In order to answer this problem, Bourdie's theory of social capital and Bandura's theory of self-affication are used. This research method is quantitative, with a focus on analyzing the influence of student social capital on the interest in entrepreneurship with self-efficacy. The analysis used in this research is simple linear regression analysis, looking for the effect of social capital variable (X) on entrepreneurial interest and self-efficacy (Y). The results obtained are social capital has a positive influence coefficient, 0.355 the higher the social capital of a student, the higher the self-efficacy, or an increase of 35.5%. Social capital has a significance t of 0.540, which means this significance is > 0.05, so social capital has no significant effect on entrepreneurial interest and self-efficacy in STPKat Semarang students. Test the coefficient of determination on the adjusted R Square value. the contribution of social capital (independent variable) 8.8% to self-efficacy, in the sense that 81.2% can be found in further research outside the social capital variable.